Investigação de fatores associados à fadiga em indivíduos com doença de Parkinson - Jessica Ramos Pereira (2015)
Introduction: Fatigue is a frequent non-motor symptom in Parkinsons disease, but its etiology remains unclear. This work evaluated the serum levels of brain-derived neurotrophic factor (BDNF) and its precursor (proBDNF), interleukin-6 (IL-6) and tumor necrosis factor alpha soluble receptors (sTNFR1 e sTNFR2) in PD patients, in presence or absence of fatigue, and the impact of fatigue in mobility and physical activity levels. Methodology: Ninety-two PD patients were recruited, and 44 were eligible according to inclusion/exclusion criteria. Patients were divided in two groups: with fatigue (fatigue group, n = 17) and without fatigue (PD group, n=27) according to Parkinson's disease Fatigue Scale (PFS-16). Results: Fatigue group showed advanced stage of the disease with higher total and subsections scores of Unified Assessment Scale of Parkinson's Disease (UPDRS). Despite time of disease after diagnosis, evaluation of depression by Beck Depression Inventary (BDI) showed higher scores in fatigue group, which also had worse functional dependence level. No difference was observed for mobility and physical activity levels by Parkinson Activity Scale (PAS) and International Physical Activity Questionnaire (IPAQ), respectively. Fatigue group had higher IL-6 serum levels (p=0,026), but no difference was found in BDNF, proBDNF, sTNFR1 or TNFR2. Discussion: Our results are in accordance to previous works that demonstrated correlation among motor deterioration, depression, and presence/intensity of fatigue. Although no difference was found in mobility and physical activity levels, this is the first study that compares these outcomes in DP patients with and without fatigue. Stage of disease and daily dose of levodopa were similar in both groups which could explain similar mobility and physical activity levels, regardless presence of fatigue. Higher levels of IL-6 in fatigue group may favor the hypothesis that neuroinflammation mechanisms are related to fatigue and to altered mechanisms of glutamatergic neurotransmission in neurological diseases. Conclusion: Our results show that DP patients with fatigue have worse clinical outcomes, despite duration of disease. Moreover, an inflammatory profile may be related to this symptom in DP patients.